The role of NGOs in empowering visually impaired people to access education and employment in Egypt - Sharaf, Nevine (AUC Knowledge Fountain, 2015)
Disability is viewed as a developmental issue given that people with disability are usually excluded from mainstream economic and social opportunities. However, the attention given to the people with disability in Egypt is mostly confined to medical and scientific features. Local NGOs in Egypt have long been working with visually impaired people. However, there is limited literature and empirical research specifying the role of local NGOs in empowering the visually impaired people to access education and employability in Egypt. Thus the purpose of this study is to assess the role that local NGOs play in this regard. The methodology used in the study is qualitative in nature and semi-structured in-depth interviews were conducted with five local Egyptian NGOs that have experienced and are already working in the field of visual impairment. The study revealed that local NGOs delivered a number of initiatives towards empowering the visually impaired through strategies that supports early intervention, providing rehabilitation services which is considered the first stop towards empowering the child with disability to access education. Strategies in terms of empowering the visually impaired to access the job market are rather limited to providing developmental training. Local NGOs do not play an adequate role in policy making. As such, the medical model of disability continues to dominate disability legislation and policy in Egypt. Thus, it is recommended that local NGOs should be moving from the medical/welfare model to a social/human rights-based model.